Dietary analysis of three species of the genus anolis (Sauria: Dactyloidae) in “los Tuxtlas,” Veracruz, Mexico - Cisneros-Bernal, Antonio Yolocalli; Jiménez-Velázquez, Gustavo; Soberon-mobarak, Francisco; Flores-Villela, Oscar A.; Vogt, Richard Carl (Revista Latinoamericana de Herpetologia, 2019)
Anoles have been studied by researchers to a greater extent than any other group of lizards. Their high diversity has led them to colonize a variety of niches, making them an ideal model group for evaluating ecological hypotheses such as dietary niche overlap. This work analyzes the stomach contents of 73 individuals from three species of the genus Anolis: A. barkeri (34), A. sericeus (17), and A. tropidonotus (22) occurring in the vicinity of Los Tuxtlas, Veracruz. Analyses performed included Shannon’s index in its log form to calculate dietary diversity, the Jaccard index to estimate the dissimilarity of the species’ diets, and Schoener’s index to measure dietary overlap. The results suggest that A. barkeri (10.08) hast the most generalist diet, followed by A. sericeus (8.75) and A. tropidonotus (5.78). Schoener’s index showed a considerable amount of diet overlap between A. barkeri and A. sericeus (0.76). We conclude that the three focal species show a generalist feeding behavior in times of abundant prey, such as the rainy season in which this study was conducted. This may lead to a reduction of interspecific competition explaining why we did not observe dietary niche displacement between these three sympatric species of Anolis. © 2019, Sociedad Herpetologica Mexicana. All rights reserved.